Abnormal uterine bleeding: a critical analysis of two diagnostic methods - Jain, Manisha; Kanhere, Anjali; Jain, Ajay Kumar Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Abnormal Uterine Bleeding (AUB) is one of the most common reasons for women to seek gynaecology consultation. The underlying causes in AUB are many and identifying the exact cause can be a real challenge to the treating gynaecologists. Objectives of current study are to study the common etiology of AUB and to study and correlate the diagnoses of Trans Vaginal Sonography (TVS) and Diagnostic Hysteroscopy (DH) with histopathology diagnosis. Methods: One hundred and thirteen women with AUB were enrolled and evaluated by conventional TVS and DH. The findings were correlated with histopathology diagnosis. The sensitivity, specificity and positive and negative predictive value of TVS and DH were calculated after comparison with final histopathology diagnosis. Results: Fibroids and polyps were the two commonest structural lesions in AUB. For submucosal fibroids, the sensitivity and specificity of DH was found to be 92% and 99% respectively while that of TVS was found to be 85 % and 100 % respectively. For polyps, the sensitivity and specificity of DH was found to be 91% and 98 % respectively and that of TVS was 68% and 93 % respectively. The coefficient of correlation for DH was better than that of TVS. Conclusions: Fibroids and polyps are the two commonest structural lesions causing AUB in the women of reproductive age group. TVS has a role as primary screening method for the initial work-up AUB before resorting to invasive procedure such as hysteroscopy.